Citizen Kane [videorecording (DVD)] - Welles, Orson, 1915-1985; Cotten, Joseph, 1905-1994; Moorehead, Agnes, 1900-1974 (Warner Home Video, 2001)
An all-powerful press magnate, Kane, dies in his fabulous castle Xanadu, his last word being "Rosebud", which leads a reporter to seek the meaning behind the word and find the meaning of Kane. Prominant publisher, William Randolph Hearst, saw the film as a thinly disguised version of his career and attempted to suppress it.